Coronary angiography in patients with native or prosthetic aortic-valve endocarditis: outcomes and implications for myocardial revascularisation. (14th October 2021) - Berger, T; Siepe, M; Dees, D; Fagu, A; Pingpoh, C; Kondov, S; Zeh, W; Beyersdorf, F.-J; Rylski, B; Schroefel, H; Czerny, M; Neumann, F.-J; et al.
Abstract: Background: Coronary angiography (CA) remains the cornerstone of the preoperative assessments before open-heart surgery to detect or rule out coronary artery disease (CAD). Preoperative CA is currently not recommended in patients with active infective aortic valve endocarditis, but may help to reduce the risk of perioperative myocardial infarction. Purpose: This study aimed to evaluate the risks and benefits of preoperative CA in selected patients before aortic valve replacement to treat active infective endocarditis of the aortic valve and to assess the incidence and relevance of CAD. Methods: Sixty-five patients with native or prosthetic aortic-valve endocarditis underwent preoperative diagnostic CA between 03/2008 and 09/2020. We collected their baseline characteristics, including the neurological status, previous cardiac surgical procedures, and reviewed the preoperative echocardiograms and the CA data. We evaluated the intraoperative data, and clinical outcomes after CA and after surgery. Patients were selected according to the site, size and mobility of vegetations of the underlying active infective process. Results: CA revealed CAD in the majority of patients (n=34; 52%): one-vessel disease n=17 (26%), two-vessel disease n=6 (9%), and three-vessel disease n=11 (17%). Coronary sclerosis without hemodynamic significance were detected in 23 patients (35%). Sixteen patients had a previous history of CAD. We observed no adverse events following preoperative diagnostic CA, particularly no thromboembolic complications, including stroke, visceral, or lower body ischaemia. Surgery was performed 3 [IQR 1; 5] days after CA. During surgical aortic-valve replacement, concomitant coronary artery bypass grafting was performed in 19 patients (29%). Postoperative in-hospital mortality was 12% (n=8) and the new-onset disabling-stroke incidence was 2% (n=1). Neither stroke nor visceral or lower body ischemia due to embolism were observed in any patient after surgery. Conclusions: By weighing risks and benefits of CA together as a team, no adverse clinical outcomes but significant clinical implications could be identified in patients with active infective aortic valve endocarditis. Concomitant surgical myocardial revascularization was frequent and may well have contributed to favorable clinical outcome. Therefore, active infective endocarditis of the aortic valve per se should not be regarded as an absolute contraindication for CA. FUNDunding Acknowledgement: Type of funding sources: None.